"They won't let us starve but they won't let us live": the politics of hunger and aid dependence in Malawi - Lowe, A (2015)
The importance of aid to economic, social and political development has been widely debated. Arguments have tended to focus either on the question of aid effectiveness or the political effects of aid. This thesis seeks primarily to contribute to the question of the political impact of aid on relationships of representation and interactions between citizens and the state; but it also demonstrates the importance of the politics of aid to its effectiveness. I take the literature on aid and politics as my starting point, which focuses on the interactions between donors and governments and the manner in which these undermine political sovereignty (Whitfield 2009; Abrahamsen 2000; Williams and Young 2012). This literature conceptualises aid interactions as taking place around a negotiating table or in the state’s bureaucracy, within a ‘sovereign frontier’ (Harrison 2007). Using Malawi’s agricultural sector – a politically important sector in a heavily aid-dependent country – as my case study, I build on this literature in two ways. Firstly, I contend that developments in aid modalities and donors’ efforts to restructure the Malawian state have resulted in more substantive infringements of sovereignty than previously argued. Donors have become constitutive of domestic politics. Aid negotiations and resistance to conditionalities now occur at all levels of the state and within domestic political systems. Thus, resistance to aid conditionalities, formal and informal, has shifted from the bureaucratic into the political realm, where it has frequently become the prerogative of the executive. Secondly, in order to fully appreciate the effects of aid dependence, primarily how it alters everyday interactions between citizens and the state, studying down the state is imperative. Here, aid dependence has profound effects on state-society relationships and political representation in Malawi, thereby preventing a move towards more responsive policy-making and away from patronage.